Accounting Systems, Participation in Budgeting, and Performance Evaluation - Penno, Mark (The Accounting Review, 1990)
[Accounting numbers are frequently used for performance evaluation because they are typically the firm's main source of formal information. As a result, employees become concerned about accounting-based budgeting processes. Whether it would be economically valuable to allow an employee to become a participant in this process is determined by the link between accounting signals and the performance expected of that employee. This article shows that by dividing activities into those that directly influence accounting measurements and those that do not, certain aspects of this link can be modeled. The results of a principal-agent analysis indicate that, in some cases, participation designed to communicate the agent's private information has no economic value even though the principal is willing to pay nonzero amounts to observe that information. The result of zero value to participation is obtained because if the agent's compensation depends only on accounting data (e.g., product cost data), any information concerning indirectly related activities may have no motivational effect on the agent and, hence, would not be useful. Conversely, if the indirectly related activities are costly to the agent (i.e., if they cause disutility), it is useful for the principal to have access to this information to adjust the agent's compensation accordingly.]